Associations between national development indicators and the age profile of people who inject drugs: results from a global systematic review and meta-analysis. Issue 1 (January 2020) - Hines, Lindsey A; Trickey, Adam; Leung, Janni; Larney, Sarah; Peacock, Amy; Degenhardt, Louisa; Colledge, Samantha; Hickman, Matthew; Grebely, Jason; Cunningham, Evan B; Stone, Jack; Dumchev, Kostyantyn; et al.
Summary: Background: Globally, an estimated 15·6 million people inject drugs. We aimed to investigate global variation in the age profile of people who inject drugs (PWID), identify country-level factors associated with age of PWID, and assess the association between injecting drug use (IDU) in young people and rates of injecting and sexual risk behaviours at the country level. Methods: We derived data from a previously published global systematic review done in April, 2016 (and updated in June, 2017) on the percentage of young PWID, duration of IDU, average age of PWID, average age at IDU initiation, and the percentage of PWID reporting sexual and injecting risk behaviours. We also derived national development indicators from World Bank data. We estimated the percentage of young PWID for each country, using a random-effects meta-analysis (DerSimonian-Laird methodology) and generated pooled regional and global estimates for all indicators of IDU in young people. We used univariable and multivariable generalised linear models to test for associations between the age indicators and country urban population growth, youth unemployment percentage, the percentage of PWID who are female, the percentage of the general population aged 15–24 years, Gini coefficient, opioid substitution therapy coverage (per PWID per year), gross domestic product (GDP) per capita (US1000), and sexual and injecting risk behaviours. Findings: In the original systematic review, data on age of PWID was reported in 741 studies across 93 countries. Globally, 25·3% (95% uncertainty interval [UI] 19·6–31·8) of PWID were aged 25 years or younger. The highest percentage of young PWID resided in eastern Europe (43·4%, 95% UI 39·4–47·4), and the lowest percentage resided in the Middle East and north Africa (6·9%, 5·1–8·8). At the country level, in multivariable analysis higher GDP was associated with longer median injecting duration (0·11 years per 1000 GDP increase, 95% CI 0·04–0·18; p=0·002), and older median age of PWID (0·13 years per 1000 increase, 0·06–0·20; p<0·0001). Urban population growth was associated with higher age at IDU initiation (1·40 years per annual percentage change, 0·41–2·40). No associations were identified between indicators of IDU in young people and youth unemployment, Gini coefficient, or opioid substitution therapy coverage provision at the country level. No associations were identified between injecting and sexual risk behaviours and age of PWID. Interpretation: Variation in the age profile of PWID was associated with GDP and urbanisation. Regions with the highest prevalence of young PWID (aged ≤25 years) had low coverage of interventions to prevent the spread of blood-borne viruses. Data quality highlights the need for improvements in monitoring of PWID populations. Funding: Australian National Drug and Alcohol Research Centre, Australian National Health and Medical Research Council, Open Society Foundation, WHO, the Global Fund, UNAIDS, National Institute for Health Research Health Protection Research Unit for Evaluation of Interventions, Wellcome Trust.